2021
DOI: 10.3832/ifor0059-014
|View full text |Cite
|
Sign up to set email alerts
|

JRC study on harvested forest area: resolving key misunderstandings

Abstract: A recent study on forest harvest in the EU (Ceccherini et al. 2020) reported a strong increase in clear-cut harvested area in recent years, based on remote sensing information. This triggered a heated debate and many critical comments. Apart from several fair and constructive criticisms, which were welcome, we found that some comments have been either not based on evidence or affected by serious misunderstandings. Here we clarify some technical aspects that were omitted or misrepresented in the public debate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The role of wood harvest and its recent trends in Europe is a controversial topic in the discussion on forest-related climate change mitigation (see e.g. [ 59 62 ]). Reducing harvesting is one of the rare alternatives available that has an immediate impact on the forest sinks in the short to medium term (i.e., few decades).…”
Section: Resultsmentioning
confidence: 99%
“…The role of wood harvest and its recent trends in Europe is a controversial topic in the discussion on forest-related climate change mitigation (see e.g. [ 59 62 ]). Reducing harvesting is one of the rare alternatives available that has an immediate impact on the forest sinks in the short to medium term (i.e., few decades).…”
Section: Resultsmentioning
confidence: 99%
“…The undocumented change in the Global Forest Change -GFC (Hansen et al 2013) algorithm between 2015 and 2016 has been already confirmed in Palahì et al (2021) and more recently in a GFC blog (GFC, 2021). The impact of that change on harvest statistics has been assessed and reported for the first time in our rebuttal and accompanying documents (i.e., Grassi et al 2021a;Ceccherini et al 2021).…”
Section: Main Textmentioning
confidence: 98%